MEDB-85. Transcriptional complexes as resistance drivers to BET inhibition. (3rd June 2022) - Boynton, Adam; Lupien, Leslie; Kumbhani, Rushil; Gionet, Gabrielle; Chacon, Madison; Goodale, Amy; Root, David; Keshishian, Hasmik; Robinson, Margaret; Carr, Steven; Bandopadhayay, Pratiti
Abstract: BET-bromodomain inhibition (BETi) is a promising therapeutic strategy to target MYC -driven cancers, including Group 3 medulloblastoma, a deadly childhood brain tumor. We have shown that BET inhibitors exhibit preclinical efficacy against MYC¬ -amplified medulloblastoma, providing motivation to evaluate this drug class in early phase clinical trials. However, our work has also found that MYC -amplified medulloblastoma cells can acquire resistance to BETi, suggesting that curative responses for this disease will require combination therapy. To guide the development of such combination therapies, we have focused our efforts on elucidating the mechanisms through which medulloblastoma cells acquire resistance to BETi. We found that medulloblastoma cells can develop tolerance to BETi by reinstating the expression of cell-essential "rescue genes, " which include bHLH transcription factors, cell-cycle regulators, and anti-apoptosis genes. This transition to the resistant cell state is mediated through changes in chromatin structure including the upregulation of H3K4me3 promoters. Our preliminary results suggest that BETi-resistant cells maintain mRNA transcription and protein translation of important mediators of resistance. Importantly, we observe that BETi-resistant medulloblastoma cells are more dependent on specific protein complexes involved in transcriptional regulation. This project explores the mechanisms through which these transcriptional regulators help maintain transcription of rescue genes that drive BETi resistance and evaluates the potential of targeting these drivers of BETi resistance. These results will help guide the development of combination approaches to improve the efficacy of BETi for the treatment of MYC -driven medulloblastoma.